Comparison of the prevalence of four coding polymorphisms of KCNH2 in healthy Kurds and Malays - Zalina, Zahari; Muslih, Abdulkarim Ibrahim; Zawiyah, Derani; Nurfadhlina, Musa (2018)
KCNH2 polymorphisms appear to be associated with arrhythmia susceptibility, drug-associated acquired long-QT syndrome and variability in drug responses. To date, little is known about the prevalence of KCNH2 polymorphisms among Kurds and Malays. As such, there is clearly a need to explore the genetic polymorphisms of KCNH2 among Kurds and Malays in order to understand the ethnic variation in KCNH2 polymorphisms. DNA was extracted from whole blood and then subjected to genotyping for KCNH2 polymorphisms, including 1539C>T (rs1805120), 1956T>C (rs1137617), 2350C>T (rs12720441) and 2690A>C (rs1805123) using nested allele-specific PCR. The 2350T allele for the 2350C>T polymorphism was absent in 487 unrelated healthy Kurds and 117 Malays. The most frequent mutant allele in Kurds was 1956C (63.9%), followed by 1539T (26.6%) and 2690C (22.4%). Frequencies of the1956C, 1539T and 2690C alleles in Malays were 80.8%, 52.6% and 8.1%, respectively. The relative commonness of mutant alleles of KCNH2 polymorphisms in our study calls attention to KCNH2 polymorphisms, which should be incorporated into future association studies in Kurds and Malays for the development of effective QT-prolonging medications.